RETRACTED: ErHuang Formula Improves Renal Fibrosis in Diabetic Nephropathy Rats by Inhibiting CXCL6/JAK/STAT3 Signaling Pathway - Shen, Yu-Li; Jiang, Yi-ping; Li, Xiao-Qin; Wang, Su-Juan; Ma, Ming-Hua; Zhang, Chun-Yan; Zhu, Jian-Yong; Rahman, Khalid; Zhang, Li-Jun; Luan, Xin; Zhang, Hong (Frontiers in Pharmacology, 2020)
Diabetic nephropathy (DN) is one of the main causes of renal fibrosis and is associated with high morbidity and mortality. Traditional Chinese Medicine (TCM) therapy has a long history of usage in a clinical setting and its usage is increasing. ErHuang Formula (EHF), a Chinese herbal compound, has been clinically used in treating DN for more than 30 years. However, its mechanism of action is still unknown. This study was conducted to evaluate the effect of EHF on renal fibrosis in a DN rat model and explore its underlying mechanism. The DN rat model was established by high-sugar-fat diet combined with a single intraperitoneal injection of streptozotocin (STZ), and EFH extract (4, 2, 1 g/kg d−1) was administered orally for 8 weeks. The biochemical parameters (blood glucose, weight, Scr, BUN, UA, U-Alb and UAE) were analyzed. The pathological changes in renal tissue were observed by histological staining with H&E and Masson. The effect of EHF on the proliferation of NRK-49F cells was examined by CCK-8 assay and the levels of several inflammation and fibrosis related cytokines (IL-6, TNF-α, TGF-β1, Collagen I/III, MMP2/9) in serum and NRK-49F cell culture supernatants were detected by enzyme-linked immunoassay (ELISA). The mRNA levels of CXCL6, CXCR1, Collagen I/III, MMP2/9 in renal tissue were also measured by quantitative RT-PCR. Furthermore, the protein expression of PCNA, Collagen I/III, MMP2/9, CXCL6, CXCR1, p-STAT3, STAT3 in renal tissue and NRK-49F cells were determined by western blot. EHF improved the abnormal biochemical parameters and ameliorated the abnormal histology and fibrosis of renal tissue in a dose-dependent manner. EHF inhibited NRK-49F proliferation and decreased the expressions of inflammation and fibrosis related factors both in vitro and in vivo. Interestingly, the levels of Collagen I/III, PCNA, MMP2/9 and p-STAT3 were positively correlated with CXCL6. The amelioration of renal fibrosis in DN by EHF is related to CXCL6/JAK/STAT3 signal pathway, which is associated with inflammation and fibrosis of the tissue. These findings may have clinical implications for the treatment of DN.